Multiplikasi Anggrek Bulan (Dendrobium sp.) Dengan Penambahan Ekstrak Taoge Dan Benzyl Amino Purine (BAP) Secara InVitro - Elvi Rusmiyanto Pancaning Wardoyo, Lisa Triyuni Arti, Mukarlina, (Jurnal Protobiont, 2017)
Dendrobium Orchid (Dendrobium sp.) is a plant with high aesthetic and economic value. Multiplication of Dendrobium Orchid can be carried out through the separation of saplings or In Vitro Multiplication. Multiplication is an activity to multiply the number of new plant by stimulating the growth of shoots, either directly or through induction of callus, to produce the same plants as the parents, and to obtain a high number of seeds in a shorter time by utilizing growth regulator, Sprout Extract and BAP. The objective of the research is to find out the effect of Sprouts Extract and Benzyl Amino Purine (BAP)on the growth of shoots in multiplication of Dendrobium Orchid and to find out the best Sprouts Extract and BAP concentration for the growth of shoots in multiplication of Dendrobium Orchid. This research was carried out for 2 (two) months from December 2016 to February 2017 in Tissue Culture Laboratory, Aloe Vera Center Pontianak. This research used completely randomized design with 2 (two) factors, namely the first factor Sprouts Extract (0%, 5%, 7,5%, and 10%), and the second factor BAP (0 M, 10-6 M, and 10-7 M). The results show that the single treatment of Sprouts Extract, the single treatment of BAP, and interaction treatment of Sprouts Extract and BAP statistically do not influence of shoots, leaves, and roots.